Congenital Tracheal Stenosis: A Rare Life-Threatening Condition - Teixeira,Sofia (2022)
Abstract Congenital tracheal stenosis (CTS) is a rare and life-threatening condition, defined as an intrinsic narrowing of the tracheal lumen caused by complete tracheal cartilage rings. The diagnosis is almost always established during childhood, due to airway obstruction. CTS is usually associated with other congenital anomalies, the vast majority being cardiovascular. Computerized tomography (CT) plays an important role in the diagnosis of CTS, as well as in determining the length of the stenosis and the caliber of the tracheal lumen, fundamental elements for the management and increase in survival. The typical imaging findings are circumferential narrowing of the trachea and fusion of the cartilaginous tracheal rings posteriorly, giving an appearance of an O-shaped trachea on an axial image. We report a case of CTS diagnosis in a child with Tetralogy of Fallot, that was admitted to the emergency room with severe respiratory distress, requiring invasive mechanical ventilation.